Keefektifan Model Brain Based Learning Terintegrasi Kearifan Lokal untuk Meningkatkan Hasil Belajar Kognitif dan Motivasi Peserta Didik Pada Topik Usaha Energi - Wulandari, Novita; Perdana, Riki (Jurnal Pendidikan Matematika dan Sains, 2023)
This research aims to determine the effectiveness of the brain based learning model integrated with local wisdom on cognitive learning outcomes and student motivation. The type of research used was a quasi-experiment with a nonequivalent control group design. The sample in the study was determined using the cluster random sampling technique. The instruments used in the research consisted of teaching modules, student worksheets, cognitive learning outcomes tests, and motivation questionnaires which were valid and reliable. Descriptive analysis techniques are carried out by classifying categories of cognitive learning outcomes and student motivation. Meanwhile, inferential analysis was carried out by testing the effect of the learning model applied on cognitive learning outcomes and student motivation. The research results show that there is an influence and increase in cognitive learning outcomes by 53% and student motivation by 52%. Based on the results of the analysis, it can be concluded that the brain based learning model is more effective in improving cognitive learning outcomes and student motivation compared to the direct instruction model.